A national COVID-19 quarantine survey and its impact on the Italian sports community: Implications and recommendations - Fiorilli, G.; Grazioli, E.; Buonsenso, A.; Di Martino, G.; Despina, T.; Calcagno, G.; Di Cagno, A. (PLOS ONE, 2021)
The outbreak of the 2019 coronavirus disease (COVID-19) created an international public health emergency, challenging the psychological resilience of the general population. Regarding this matter, a web-based survey was performed. Data were collected from the following 1,668 self-selected volunteers: 800 athletes (28.30 ± 10.93 years old); 558 coaches (36.91 ± 11.93 years old); and 310 sports managers (42.07 ± 13.38 years old). To assess the level of psychological stress, an Impact of the Event Scale-Revised (IES-R) questionnaire was used. The results indicated that 34.4% of the participants who were interviewed were affected by subjective distress while 26.4% rated their psychological impact from the sports activity interruption as severe. Separated one-way analysis of variance (ANOVA) tests showed significant differences in the IES-R total score (TS), indicating that the level of stress in terms of gender revealed that women were more stressed than men (p = 0.000), for "sports roles" in which the manager and coaches were more stressed than the athletes (p < 0.05), and "type of sport" in which fitness and individual athletes were more stressed than team athletes (p < 0.01). The middle-level athletes showed significantly more hyperarousal levels than high-level athletes (p = 0.012). The results of this survey may raise awareness of this problem and help athletic associations to have appropriate guidelines in order to better sustain their memberships and organize an optimal resumption of their sports activities. Along these lines, social interactions, which are typical of team sports, are crucial to warrant resilience and psychological health. The athletes by managing independently the new rules and measures, thanks to a clear communication, could improve their adaptive stress reaction.